Innovations in recycled construction materials: paving the way towards sustainable road infrastructure - Hoy, Menglim; Horpibulsuk, Suksun; Chinkulkijniwat, Avirut; Suddeepong, Apichat; Buritatum, Apinun; Yaowarat, Teerasak; Choenklang, Punvalai; Udomchai, Artit; Kantatham, Karn (Frontiers in Built Environment, 2024)
The expansive development of infrastructure has led to increased consumption of virgin aggregates in road construction, resulting in significant environmental impacts. To address this issue, there is a pressing need for sustainable alternatives that utilize recycled materials in pavement applications. This paper presents a comprehensive review of a decade-long research program focused on the development and evaluation of sustainable pavement materials, such as recycled and waste aggregates, industrial by-products, and natural fibers. The research encompassed a wide range of innovative materials and technologies, such as geopolymer-stabilized recycled aggregates, cement-stabilized waste materials, natural additive-modified cement stabilization, and recycled aggregate-geogrid reinforcement systems. The experimental framework employed a combination of mechanical testing, durability assessment, microstructural analysis, and environmental safety evaluation to assess the performance and sustainability of these materials. The key findings demonstrated the superior mechanical properties, improved durability, and environmental suitability of the recycled materials compared to conventional virgin aggregates. The successful implementation of these sustainable solutions in real-world projects highlights their potential to reduce the environmental footprint of road infrastructure development. Furthermore, the paper discussed the practical implications of the research outcomes for pavement design and construction, as well as future research directions to further advance the field of sustainable pavement engineering. The findings of this research report can be used as guidance for researchers, practitioners, and policymakers seeking to upcycle the widespread adoption of recycled materials in road application and contribute to the development of a more sustainable and resilient transportation infrastructure.